Digital-based home industry and MSMEs management in Sidowayah Village - Afni, Ika Nur; Winarti, Liliek; Wirawan, Riska (Universitas Muhammadiyah Magelang, 2021)
Home industry and MSMEs in Sidowayah Village, Polanharjo District, Klaten Regency are not fully developed. There are several productions of processed food and household crafts that are less than optimal, both in terms of production and marketing. Some of the problems related to marketing are that there is no digitalization yet. Some MSMEs have to go out of business during the Covid-19 pandemic. Even though during the Covid-19 pandemic, there is great potential to increase sales and ensure the continuity of product marketing from community-owned businesses. The results of the socialization activities related to the management of the home industry and MSMEs made them understand the urgency of digitizing MSMEs as an effort to widen their industrial market and to improve welfare and economic recovery during the pandemic.